“Perspektif”: Sebuah Komposisi Jazz untuk Band Kombo - Kevin Valencio Suwandi; Ketut Sumerjana; I Wayan Suweca (Institut Seni Indonesia Denpasar, 2022)
Purpose: In this modern jazz composition entitled “Perspektif”, composers were exploiting 3 major aspects of music, which is: rhythm, melody and harmony. The main purpose in this piece is to persuade other composers to not only think creatively but to maximize and research deeply all the basic aspects of music. Research Methods: Modern jazz music can’t be separated from the old school jazz and classical music. The key to be making innovative and creative composition was by learning the music from the previous era. Results and Discussion: By learning the history and research deeply into all the basic aspects of music, the composers can easily come up with something innovative and creative, which in this case is combining jazz music instruments with different kind of sports as non-musical instrument. However, not only it features the sound of the sport but also playing advanced rhythm and filling the space what the music instruments can’t do. Implication: In the process of making this composition from 3 major aspects in music, the composers got enlightened that all of each aspect has many different ways to be looked at or played at. Since the composers named this piece “Perspektif” with a format of 4 pieces jazz combo, 2 guys playing badminton, 1 guy playing basketball and the other 2 doing boxing.